Early and late-recorded predictors of health-related quality of life of burn patients on long-term follow-up. Issue 6 (September 2019) - Gojowy, David; Kauke, Martin; Ohmann, Tobias; Homann, Heinz-Herbert; Mannil, Lijo
Highlights: The HRQoL of major long-term burn survivors seems to normalize over time. Increased age at admission and poor scar quality negatively influenced the HRQoL. Positive affect and a high degree of social support positively influenced the HRQoL. Abstract: Background: Unintentional and intentional burn injuries vary across age groups, gender, income, and global region. In high-income countries, the trend over the last several years has been a reduction in burn incidence, burn severity, length of hospital stay, and mortality rate. However, there is a lack of data on predictors of the health-related quality of life (HRQoL) of major burn survivors extending beyond a follow-up period of 10 years. Patients and methods: This single-center cross-sectional study is considering 42 long-term severe burn survivors with deep partial thickness burns and an affected total body surface area (TBSA) of ≥20%. For study eligibility design a minimum follow-up of 10 years was obligatory. Entitled individuals were asked to fill in the generic Short Form 36 (SF-36) questionnaire. The physical (PCS) and mental (MCS) component scores of the SF-36 were used as the primary outcome variables. Putative predictor variables were drawn from medical records. Burn-specific functionality and scar tissue quality were assessed using the Burn Specific Health Scale-Brief (BSHS-B) questionnaire and the Patient and Observer Scar Assessment Scale (POSAS), respectively. Correlation between putative predictor variables and SF-36 norm scores were evaluated by Pearson- and Point-Biserial correlation as well as multivariate linear regression. The SF-36 norm scores were compared to the general German population. Results: Mean follow-up was 14 (±3) years with a minimum and maximum of 10 and 28 years, respectively. Mean age at the time of the incident was 37 (±17) years. The majority of individuals were male (74%). The mean burn size was 39 (±17) % (TBSA) with 76% of the individuals showing a full thickness burn. SF-36 norm scores were not statistically different from the general population. Statistically significant independent predictor variables of the physical summary score were: age at the time of the injury (−0.381), time since injury (−0.466), length of hospital stay (−0.356), limb amputation (−0.318), unemployment (−0.433), work (0.593), hand function (0.601), body image (0.518), affect (0.355), simple abilities (0.602), burns involving the hands (−0.339) and back (−0.343), POSAS patient- (−0.521) and observer scores (−0.483). In multivariate analysis, work (4.315), the POSAS Score (−2.082) and the age at the time of the incident (−0.242) were statistically significant predictors. Statistically significant independent predictor variables of the mental summary score were: duration of mechanical ventilation (−0.459), hand function (0.415), body image (0.502), sexual activity (0.625), social support (0.542), burns involving the back (−0.315) and affect (0.692). In multivariate analysis, affect (13.844) and the length of mechanical ventilation (−0.115) were statistically significant independent predictor variables. Conclusion: Ten years after the burn incident, the quality of life was on average comparable to the one in the general population. Multiple variables seem to influence the physical and mental long-term outcome. Herein presented data may support in adapting and designing follow-up strategies tailored to a patient's burn-specific circumstances.